Learning, retention, and forgetting of Newton’s third law throughout university physics - Sayre, Eleanor C.; Franklin, Scott V.; Dymek, Stephanie; Clark, Jessica; Sun, Yifei (My University, 2012)
We present data from a between-student study on student response to questions on Newton’s third law given in two introductory calculus-based physics classes (Mechanics and Electromagnetism) at a large northeastern university. Construction of a response curve reveals subtle dynamics in student learning not capturable by pretesting and post-testing. We find a significant positive effect of instruction that diminishes by the end of the quarter. Two quarters later, a significant dip in correct response occurs when instruction changes from the vector quantities of electric forces and fields to the scalar quantity of electric potential. When instruction returns to vector topics, performance rebounds to initial values.
Keywords: Response curves method; Student learning; Forgetting; Interference; Newton’s third law